The importance of using interactive methods in developing the creative competence of primary school students - Bobur Abdugani oglu Nabiyev (Science and Education, 2025)
This article analyzes the pedagogical, psychological, and methodological significance of an interactive environment in the process of developing the creative competence of primary school students. The study substantiates that creating an interactive learning environment is an essential factor in developing students’ independent thinking, creative approach, and problem-solving skills. The mechanisms of organizing students’ activities through interactive methods, relying on their personal experience, and acquiring knowledge through collaboration are also examined from a scientific perspective.